PENGEMBANGAN BUKU CERTAGAM UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN PADA SISWA KELAS II SD NEGERI PULUTAN 02 - Ana Septianingsi; Henny Dewi Koeswanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a picture storybook called Certagam as an instructional medium to improve reading comprehension skills of second-grade students at SD Negeri Pulutan 02. The research used a Research and Development (R&D) method based on the ASSURE model. The development process included three main stages: preliminary study, product development, and limited trial. Data collection instruments included expert validation (material, media, and design) as well as pretest and posttest among students. The validation results showed that the Certagam book received a "very high" category from all experts. The effectiveness test results indicated a significant improvement between pretest and posttest scores based on the Wilcoxon test (p < 0.05). These findings demonstrate that the Certagam book is effective for teaching reading comprehension. This research also reinforces previous studies showing that picture storybooks can enhance literacy and student engagement in primary education